2016
DOI: 10.1002/adhm.201600868
|View full text |Cite
|
Sign up to set email alerts
|

NIR‐Mediated Nanohybrids of Upconversion Nanophosphors and Fluorescent Conjugated Polymers for High‐Efficiency Antibacterial Performance Based on Fluorescence Resonance Energy Transfer

Abstract: A novel nanohybrid comprised of upconversion nanophosphors (UCNPs) and fluorescent conjugated polymers (PFVCN) is rationally fabricated. The new UCNP/PFVCN nanohybrids combine the excellent antibacterial ability of PFVCN and the near IR (NIR) absorbing property of UCNPs, which allows for NIR-mediated antibacterial through the effective fluorescence resonance energy transfer from UCNPs to PFVCN accompanied with generation of reactive oxygen species to kill bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 36 publications
0
31
0
Order By: Relevance
“…Besides, the CPs-PDT system can be excited by the NIR laser, which can bypass the penetration issues and was explored for cancer therapy in the deeper tissues. [164,165] Benefited from the excellent light-harvesting of CPs, the energy transferred from CPs to PSs (e.g., porphyrin) can dramatically enhance the ROS production efficiency. Based on the energy transfer mechanism, Wu et al recently reported an energy-transfer amplified Pdots which can generate singlet oxygen for in vivo PDT.…”
Section: Photodynamic Therapymentioning
confidence: 99%
“…Besides, the CPs-PDT system can be excited by the NIR laser, which can bypass the penetration issues and was explored for cancer therapy in the deeper tissues. [164,165] Benefited from the excellent light-harvesting of CPs, the energy transferred from CPs to PSs (e.g., porphyrin) can dramatically enhance the ROS production efficiency. Based on the energy transfer mechanism, Wu et al recently reported an energy-transfer amplified Pdots which can generate singlet oxygen for in vivo PDT.…”
Section: Photodynamic Therapymentioning
confidence: 99%
“…In 2016, Tang's group designed and synthesized a hybrid nanomaterial. 53 This new material combines a water-soluble conjugated polymer and an up-conversion nanomaterial. Under the illumination of the NIR light source, which can penetrate deep tissue, photodynamic therapy (PDT) of this hybrid nanomaterial is achieved to generate reactive oxygen species to effectively kill bacteria (Figure 9).…”
Section: Application Of Cpns In Pathogen Detectionmentioning
confidence: 99%
“…Photodynamic antibacterial therapy has been widely investigated in recent years, but the light source used restricts its application in deep infections. In 2016, Tang’s group designed and synthesized a hybrid nanomaterial . This new material combines a water-soluble conjugated polymer and an up-conversion nanomaterial.…”
Section: Application Of Cpns In Pathogen Detection and Killingmentioning
confidence: 99%
See 1 more Smart Citation
“…The traditional methods of drug therapies lead to the evolution of several drug‐resistant bacteria such as Salmonella , E. Coli , and Staphylococcus , which poses more risks to human health. To overcome this problem, the exploration of new therapeutic modalities to fight against bacterial infections or to enhance the antibacterial activity of present therapies toward drug‐resistant bacteria is of paramount importance . UCNP‐photosensitizer‐based PDT triggered by NIR light is an ideal therapeutic method for this purpose.…”
Section: Biological Applications Of Ucnpsmentioning
confidence: 99%